Choosing suppliers in North-West Russia - Malaki, Mirva (Saimaan ammattikorkeakoulu, 2013)
The purpose of the study was to determine how to choose suppliers in North-West Russia. The aim was to find out whether textbook theories of choosing suppliers can be used as such to the business circumstances of North-West Russia or whether the criteria mentioned in textbooks need to be modified by taking the special features of the business culture of North-West Russia into account. Furthermore, the reason was to find out how to manage risks related to supplier choice. This study was carried out by interviewing experienced business practitioners that have had strong background in business in North-West Russia. Qualitative approach was conducted in semi-structured interviews. Hypothesis of this study was that it is not possible to use purchasing books as sole source of information when choosing suppliers in North-West Russia. Based on the findings of the study, purchasing books should not be used as sole source when choosing suppliers in North-West Russia. Choosing suppliers is not an easy task to manage and there are many different problematic items to handle. Risk management in North-West Russia is also challenging, but can be managed if there is total control of each step in the supply chain. Further study is required to find out how much the result would vary when taking into account a specific field of business.